2016
DOI: 10.2147/dddt.s106216
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal administration of elastin-like polypeptide for therapeutic delivery to the central nervous system

Abstract: Bypassing the blood–brain barrier is one of the primary considerations when designing compounds intended to function in the central nervous system (CNS). Intranasal (IN) administration of otherwise blood–brain barrier impermeable molecules can result in high CNS concentrations and low systemic accumulation, indicating that IN administration may be a useful method of delivering therapeutics to the CNS. Elastin-like polypeptide (ELP) is a large, non-immunogenic, highly manipulable biopolymer with extensive evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…administration when compared to i.v. : (i) there was higher accumulation in the brain [ 51 ] and (ii) the accumulation was less spread, enabling targeting of the nanoparticles to more specific CNS regions, which is associated with the nanoparticle properties [ 56 ] and probably with the type of nasal nanoformulation [ 54 ]. After i.n.…”
Section: Resultsmentioning
confidence: 99%
“…administration when compared to i.v. : (i) there was higher accumulation in the brain [ 51 ] and (ii) the accumulation was less spread, enabling targeting of the nanoparticles to more specific CNS regions, which is associated with the nanoparticle properties [ 56 ] and probably with the type of nasal nanoformulation [ 54 ]. After i.n.…”
Section: Resultsmentioning
confidence: 99%
“…Further, in this report we demonstrate that ELPs are retained in one target tissue for durations as long as two weeks. In addition, by leveraging intra-vitreal administration the likelihood of off-target drug effects will be minimized as recently reported for intranasal delivery [53]. Previous studies have demonstrated that apoptosis plays an important role in RPE degeneration in NaIO 3 challenged mice, and that αB crystallin has anti-apoptotic effects [4,6,27,35,39].…”
Section: Discussionmentioning
confidence: 99%
“…ELPs fused with neurotrophin served as a drug depot, limiting neurotrophin loss due to diffusion, and allowed controlled spatio-temporal drug delivery [83]. Moreover, the tuneable characteristics of ELPs allowed intranasal administration aimed at therapeutic delivery of drugs to the CNS [84].…”
Section: Natural Polymers For Neural Tissue Engineeringmentioning
confidence: 99%